1998
DOI: 10.1080/080352598750030898
|View full text |Cite
|
Sign up to set email alerts
|

Impact of zinc supplementation on persistent diarrhoea in malnourished Bangladeshi children

Abstract: To evaluate the impact of zinc supplementation on the clinical recovery and body weight of children with persistent diarrhoea, a randomized, double-blind, controlled trial was conducted in 190 children with persistent diarrhoea aged between 3 and 24 months. Children were randomly allocated to receive either zinc (20 mg d(-1)) syrup with multivitamin (2 x RDA) or multivitamin alone in three divided daily doses for 2 weeks. The trial was conducted in a diarrhoeal disease hospital in Dhaka, Bangladesh. Duration u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The clinical benefits of zinc supplementation in these children with persistent diarrhoea were early recovery especially in underweight and male children described earlier (16). A significantly higher number of children also dropped out from the placebo group due to prolonged suffering.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The clinical benefits of zinc supplementation in these children with persistent diarrhoea were early recovery especially in underweight and male children described earlier (16). A significantly higher number of children also dropped out from the placebo group due to prolonged suffering.…”
Section: Discussionmentioning
confidence: 54%
“…The participants were children of both sexes, aged 3–24 months, who were previously treated with zinc or placebo during persistent diarrhoea (16). Children who attended the Clinical Research and Service Centre (now Dhaka Hospital) of ICDDR,B, during 1987–1989, were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Five trials were on children with persistent diarrhoea (Sachdev 1990; Roy 1998; Bhutta 1999; Penny 1999; Khatun 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Several controlled zinc-treatment trials over the past decade have demonstrated the beneficial role of zinc in the prevention and treatment of diarrhoea (1-3,6-9,44,45). Meta-analyses of these trials estimate that children, aged three months to five years, who receive zinc for the treatment of a diarrhoeal illness (20 mg/day for 10 days), recover faster and experience a 30% reduction in the likelihood of developing prolonged diarrhoea.…”
Section: Effects Of Zinc Supplementationmentioning
confidence: 99%
“…Since then, several randomized hospital- and community-based trials have consistently demonstrated the efficacy of zinc treatment for acute or persistent diarrhoea in children aged less than five years (under-five children) (3-6). Pooled analyses of published data demonstrate that zinc reduces the duration and severity of acute diarrhoea and the likelihood of a prolonged episode (7,8).…”
Section: Introductionmentioning
confidence: 99%